The Capacity of Feeling Loved Predicted Life Satisfaction and Positive Affect in Married Individuals - Edwin Adrianta Surijah; Kadek Dilan Ari Rahayu; Supriyadi - (Universitas Andalas, 2020)
Love is an indispensable part of human life, and this study specifically investigated the expression of feeling loved. This study aims to explore the association between couples’ feeling loved and different components of wellbeing. We constructed a continuous rating scale to measure couples’ feeling loved and its contribution toward life satisfaction and positive affect. There were 252 couples participated in this study. To examine the measurement’s consistency, this study compared the continuous rating scale of feeling loved with its Likert scale and rating scale counterpart. This study also investigated the role of feeling loved towards the scores of positive affect and life satisfaction as the components of wellbeing. Actor partner interdependence model and linear regression results showed that feeling loved was positively contributed to life satisfaction and positive affect; however, there was no significant interactive effect within partner. This study suggested feeling loved influenced wellbeing, although other predictors may play more prominent roles in determining wellbeing. Keywords: love, feeling loved, wellbeing